Flexible Co-Planar Waveguide (CPW)-fed y-shaped patch UWB antenna for off-body communication - S., Kassim; Hasliza, A. Rahim; P. J., Soh; Mohamedfareq, Abdulmalek; M., Jusoh; M. H., Jamaluddin; Nur Syahirah, Sabli; M. N., Yassin; T., Sabapathy; F. H., Wee; M. N., Osman; Noormariani, Ismail (IOP Publishing, 2019)
This paper intends to design an Ultra-Wideband (UWB) antenna for future Internet of Things (IoT) applications for off-body Wireless Body Area Networks (WBAN) communication. An antenna based on the Y-shaped patch fed using co-planar waveguide (CPW) line, with a full ground plane is designed. It is implemented on two different substrates, namely a 5mm thick Rogers RO4350B and a 5-mm-thick felt textile. Parametric analysis of antenna is performed by changing its critical dimensions and monitoring parameters such as gain, bandwidth, efficiency, radiation pattern when using both substrates. Besides that, the bending effects towards reflection coefficient and radiation patterns are also studied. The final patch size with the Y-shaped slot is 36 × 40 mm2 for both substrates. The antenna is capable of providing coverage for the bands from 8 to 10 GHz. Finally, the antenna designed on RO4350B substrate outperforms the antenna designed on felt by about four times in terms of bandwidth, with 3.3 GHz (7.7–11 GHz).